Контакти осілого населення дніпро-донецького лісостепу з сарматами в середині I — середині III ст. - Любичев, М.В. (Археологія, 2008)
Статтю присвячено розгляду контактів осілого населення дніпро-донецького лісостепу ступенів В2—С1а —носіїв пізньозарубинецько-ранньокиївських пам’яток, та сарматів Подніпров’я і Подоння. Контакты сарматов с позднезарубинецко-раннекиевским населением в зоне лесостепи и прилегающей полосе степи были еще более ограниченными, чем в предшествовавший период позднего латена контакты между носителями зарубинецкой культуры и сарматами. Создается впечатление, что контакты между ними ограничивались лишь захватом сарматами пленных из позднезарубинецких и раннекиевских поселений. В период до появления в регионе черняховской культуры здесь не происходило интеграции сарматов с оседлым населением. Contacts of Sarmatians with Late Zarubincy — Early Kiev of the population in a zone of forest-steppe and in an adjoining strip of steppe were even more limited, than during the previous period late Laten contacts between carriers Zarubincy cultures and Sarmatians. These of a generality are looked as not perceiving each-other, but at the same time separate Sarmatian burials are deeply in forest-steppe (Borisovka). The impression is made, that contacts between them were limited only to capture by Sarmatians captured from among inhabitants Late Zarubincy and Early Kiev settlements. During before occurrence in region Chernyachov cultures here did not occur any integration of Sarmatians to settled population.